Methods used in preclinical assessment of anti-Buruli ulcer agents: A global perspective - Tsouh, P.V.F.; Addo, P.; Yeboah-Manu, D.; Boyom, F.F. (Journal of Pharmacological and Toxicological Methods, 2015)
Buruli ulcer (BU) caused by Mycobacterium ulcerans is the third most common chronic mycobacterial infection in humans. Approximately 5000 cases are reported annually from at least 33 countries around the globe, especially in rural African communities. Even though anti-mycobacterial therapy is often effective for early nodular or ulcerative lesions, surgery is sometimes employed for aiding wound healing and correction of deformities. The usefulness of the antibiotherapy nonetheless is challenged by huge restrictive factors such as high cost, surgical scars and loss of income due to loss of man-hours, and in some instances employment. For these reasons, more effective and safer drugs are urgently needed, and research programs into alternative therapeutics including investigation of natural products should be encouraged. There is the need for appropriate susceptibility testing methods for the evaluation of potency. A number of biological assay methodologies are in current use, ranging from the classical agar and broth dilution assay formats, to radiorespirometric, dye-based, and fluorescent/luminescence reporter assays. Mice, rats, armadillo, guinea pigs, monkeys, grass cutters and lizards have been suggested as animal models for Buruli ulcer. This review presents an overview of in vitro and in vivo susceptibility testing methods developed for the determination of anti-Buruli ulcer activity of natural products and derivatives. Copyright © 2015. Published by Elsevier Inc. Methods used in preclinical assessment of anti-Buruli ulcer agents: A global perspective | Request PDF. Available from: https://www.researchgate.net/publication/273779095_Methods_used_in_preclinical_assessment_of_anti-Buruli_ulcer_agents_A_global_perspective [accessed Sep 18 2018].
Keywords: Methods; Preclinical; Buruli ulcer; Assays; Animal models